Korean Students and Games in the Spanish as a Foreign Language Classroom. A Viable Combination? (Ogigia. Revista Electrónica de Estudios Hispánicos, 2019)
After a systematic use of games for teaching Spanish in South Korea, this paper offers an approach to students ́ perception of this active learning tool. Considering the results of a game perception survey distributed among undergraduate students, the viability of this resource with SFL lessons will be discussed.
Keywords: Games; SFL; Perception; South Korea; Student